2015
DOI: 10.1186/s11671-014-0726-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of architectures and H2O2 additions on the photocatalytic performance of hierarchical Cu2O nanostructures

Abstract: Cu2O hierarchical nanostructures with different morphologies were successfully synthesized by a solvothermal method using copper (II) nitrate trihydrate (Cu(NO3)2⋅3H2O) and ethylene glycol (EG) as initial reagents. The obtained nanostructures were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) specific surface area test, and UV-vis spectroscopy. The synthesis conditions (copper source, temperature, and reaction time) dominated the compositions and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…The experiment results indicated that the photocatalytic activities could be significantly affected by Sn The photocatalytic mechanism of undoped and Sn-doped Cu 2 O could be reasonably proposed, which were similar to previous reports [41]. Visible light irradiation on the surface of Cu 2 O can generate electron-hole pairs due to the electron exciting from valance band (VB) to conductance band (CB), and thus, a number of reactions could be induced by the photogenerated electrons and holes as previously reported [15,18,41,47] ‫ݑܥ‬ ଶ ܱ + ℎ߭ → ݁ ି ‫ݑܥܤܥ‪ሺ‬‬ ଶ ܱሻ + ℎ ା ‫ݑܥܤܸ‪ሺ‬‬ ଶ ܱሻ (10) The photogenerated holes and electrons can react with H 2 O to generate oxidant species such as·OOH, ·OH, and ·ܱ ଶ ି [15]. Then, the dyes (MO)…”
Section: Photocatalytic Activitysupporting
confidence: 80%
“…The experiment results indicated that the photocatalytic activities could be significantly affected by Sn The photocatalytic mechanism of undoped and Sn-doped Cu 2 O could be reasonably proposed, which were similar to previous reports [41]. Visible light irradiation on the surface of Cu 2 O can generate electron-hole pairs due to the electron exciting from valance band (VB) to conductance band (CB), and thus, a number of reactions could be induced by the photogenerated electrons and holes as previously reported [15,18,41,47] ‫ݑܥ‬ ଶ ܱ + ℎ߭ → ݁ ି ‫ݑܥܤܥ‪ሺ‬‬ ଶ ܱሻ + ℎ ା ‫ݑܥܤܸ‪ሺ‬‬ ଶ ܱሻ (10) The photogenerated holes and electrons can react with H 2 O to generate oxidant species such as·OOH, ·OH, and ·ܱ ଶ ି [15]. Then, the dyes (MO)…”
Section: Photocatalytic Activitysupporting
confidence: 80%
“…To measure the photodegradation activity, a plot of the photodegradation rate constant of RhB versus degradation time was used. The reaction can be described as a pseudo-first-order kinetics model as follows [9]:where C 0 represents the initial concentration of RhB, C refers to the concentration of RhB at different irradiation times t , and k is the reaction rate constant. The linear plots of ln( C / C 0 ) versus time of the photodegradation of RhB over ZnO, NiO, ZN1, ZN2, and ZN3 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typical semiconductors that have been investigated are TiO 2 [4], ZnO [57], Cu 2 O [8, 9], CdS [10, 11], and C 3 N 4 [12]. Among them, ZnO has been the most systemically investigated owing to its high electron mobility, diverse morphologies, ease of preparation, low cost, and non-toxic nature [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Cuprous oxide (Cu 2 O), another important transition metal oxide, as a reddish p-type semiconductor with a direct forbidden band gap 2.17 eV, has a various applications in photo-catalysis [5], sensors [6], solar cells [7], CO oxidation, and lithium-ion batteries [8]. As used in lithium-ion batteries, Cu 2 O was regarded as a promising anode material due to some temptation advantages, such as its reversible mechanism with Li ?…”
Section: Introductionmentioning
confidence: 99%